Neonatal Transitions in Social Behavior and Their Implications for Autism. Issue 5 (May 2018) - Shultz, Sarah; Klin, Ami; Jones, Warren
Abstract : Within the context of early infant–caregiver interaction, we review a series of pivotal transitions that occur within the first 6 months of typical infancy, with emphasis on behavior and brain mechanisms involved in preferential orientation towards, and interaction with, other people. Our goal in reviewing these transitions is to better understand how they may lay a necessary and/or sufficient groundwork for subsequent phases of development, and also to understand how the breakdown thereof, when development is atypical and those transitions become derailed, may instead yield disability. We review these developmental processes in light of recent studies documenting disruptions to early-emerging brain and behavior mechanisms in infants later diagnosed with autism spectrum disorder, shedding light on the brain–behavior pathogenesis of autism. Highlights: From the first moments of life, neonates exhibit a range of socially adaptive preferences and reflex-like responses that serve to orient their attention towards caregivers, as well as behaviors that serve as important signals to those caregivers. Within the first 6 months of typical infancy, a series of pivotal transitions occur within the context of early infant–caregiver interaction, as initially spontaneous reflex-like responses transition into remarkably sensitive and contingent social action. Recent reports suggest that these developmental transitions may be disrupted in autism spectrum disorder, opening a critical theoretical insight into understanding the brain–behavior pathogenesis of autism.